2023
DOI: 10.3390/biomedicines11051325
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling Modulates Activity of Immune Checkpoint Inhibitors in Cancer Patients

Abstract: Although immunotherapy is already a staple of cancer care, many patients may not benefit from these cutting-edge treatments. A crucial field of research now focuses on figuring out how to improve treatment efficacy and assess the resistance mechanisms underlying this uneven response. For a good response, immune-based treatments, in particular immune checkpoint inhibitors, rely on a strong infiltration of T cells into the tumour microenvironment. The severe metabolic environment that immune cells must endure ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 263 publications
(294 reference statements)
0
4
0
Order By: Relevance
“…In RCC, it has been documented that the response to cellular stress interferes with ROS production, angiogenesis, mitochondrial quality, tumor metabolism, inflammation, genetic instability, and the tumor microenvironment (TME) [8,10,[20][21][22]. Low levels of chronic oxidative stress act as a driving force for the malignant transformation of renal epithelial cells [15,23,24].…”
Section: Cellular Stress In Rcc Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…In RCC, it has been documented that the response to cellular stress interferes with ROS production, angiogenesis, mitochondrial quality, tumor metabolism, inflammation, genetic instability, and the tumor microenvironment (TME) [8,10,[20][21][22]. Low levels of chronic oxidative stress act as a driving force for the malignant transformation of renal epithelial cells [15,23,24].…”
Section: Cellular Stress In Rcc Biologymentioning
confidence: 99%
“…Potential pathogenic mechanisms include drug-induced neoantigen formation, unmasking of usually hidden autoantigens, and generalized activation of CD4+ and CD8+ T cells, leading to diffuse keratinocyte apoptosis [121]. Cutaneous immune-related adverse events induced by immune checkpoint inhibitors can be grouped as follows: (a) inflammatory dermatoses (maculopapular eruptions) and papulosquamous disorders (pityriasis rosea, pityriasis lichenoides, pityriasis rubra pilaris, lichenoid and psoriasiform lesions); (b) immune bullous dermatoses (bullous pemphigoid, linear IgA dermatosis); (c) melanocyte alterations (vitiligo-like skin depigmentation, tumoral melanosis and regression of melanocytic nevi, poliosis, and eyebrow or eyelash depigmentation); (d) keratinocyte alterations (benign, precancerous, and cancerous keratinocytic lesions, mainly on photodamaged skin, seborrheic keratoses, actinic keratoses, keratoacanthomas, basal or squamous cell carcinomas); (e) hair abnormalities (non-scarring alopecia, partial or diffuse alopecia areata, hypotrichosis, vi-tiligo, universal alopecia, hair texture changes); (f) nail involvement (nail dystrophy, mostly with psoriasiform or lichenoid features, onychomadesis and proximal onychoschizia, diffuse onycholysis and paronychia); (g) oral involvement (mucositis, gingivitis, xerostomia, dysgeusia, Sjogren syndrome); and (h) rare reactions (photosensitivity, dermatomyositis, panniculitis, granulomatous dermatitis, lymphomatoid or eosinophilic cutaneous toxicity, acute generalized exanthematous pustulosis, neutrophilic dermatoses, toxic epidermal necrolysis) [22,121,[130][131][132].…”
Section: Adverse Cutaneous Drug Events In Rcc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may explain the disappointing clinical activity of immune checkpoint inhibitors in the treatment of ovarian cancer [116]. Recently, a link between the expression of CYPs and resistance to immune checkpoint inhibitors in the treatment of cancers was identified [31,117]. It was found that CYP1B1 expression promoted colon cancer cells' resistance to ferroptosis and induced resistance to anti-PD-1 therapy.…”
Section: Association Of Cyp Isoform Expression With Immune Infiltrationmentioning
confidence: 99%